2006
DOI: 10.1634/stemcells.2005-0611
|View full text |Cite
|
Sign up to set email alerts
|

POU5F1 Isoforms Show Different Expression Patterns in Human Embryonic Stem Cells and Preimplantation Embryos

Abstract: The contribution of the POU domain, class 5, transcription factor-1 (POU5F1) in maintaining totipotency in human embryonic stem cells (hESCs) has been repeatedly proven. In humans, two isoforms are encoded: POU5F1_iA and POU5F1_iB. So far, no discrimination has been made between the isoforms in POU5F1 studies, and it is unknown which isoform contributes to the undifferentiated phenotype.Using immunocytochemistry, expression of POU5F1_iA and POU5F1_iB was examined in hESCs and all stages of human preimplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
1
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 32 publications
10
121
1
5
Order By: Relevance
“…The OCT4 splice variants OCT4-A and OCT4-B share an identical C-terminal domain, whereas the recently discovered OCT4-B1 lacks the C-terminal domain because of a stop codon in the cryptic exon 2b, and consequently the IHC data we obtained were potentially related to the OCT4-A and -B isoforms. Nonetheless, because we obtained a clear nuclear localization of the IHC signal for OCT4 (Figure 3), we can argue that it corresponds to the OCT4-A variant, as it has been reported that the OCT-4B variant is localized in the cytoplasm (40,41).…”
Section: Discussionsupporting
confidence: 57%
“…The OCT4 splice variants OCT4-A and OCT4-B share an identical C-terminal domain, whereas the recently discovered OCT4-B1 lacks the C-terminal domain because of a stop codon in the cryptic exon 2b, and consequently the IHC data we obtained were potentially related to the OCT4-A and -B isoforms. Nonetheless, because we obtained a clear nuclear localization of the IHC signal for OCT4 (Figure 3), we can argue that it corresponds to the OCT4-A variant, as it has been reported that the OCT-4B variant is localized in the cytoplasm (40,41).…”
Section: Discussionsupporting
confidence: 57%
“…There are two studies (Tai et al, 2005;He et al, 2012) who had reported Oct4 expression by dysplastic and hyperplastic esophageal mucosa confining to the proliferative zone, and not expressed by the normal mucosa. Oct4 positivity is reported in certain adult tissue including benign endometrial stromal cells (Atlasi et al, 2006;Cauffman et al, 2006;Mathai et al, 2006;Katona et al, 2007;Zangrossi et al, 2007;Atlasi et al, 2008;Forte et al, 2009). We observed slightly higher sensitivity by PCR technique than by the conventional immunohistochemistry method in detecting Oct4 expression, which is similar to other reported data (Atlasi et al, 2006;Xi et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the expression of POU5F1, a pivotal transcriptional regulator of the pluripotent state in embryonic stem cells. POU5F1 exists in two isoforms, POU5F1A and POU5F1B, of which POU5F1A is nuclear-localized and transcriptionally active [8,17]. But, the POU5F1B isoform, which lacks the N-terminal transactivation domain (supplemental online Fig.…”
Section: Discussionmentioning
confidence: 99%
“…But, the POU5F1B isoform, which lacks the N-terminal transactivation domain (supplemental online Fig. 5), is localized mainly in the cytoplasm of human ESCs [17] and, more importantly, does not sustain self-renewal of ESCs [19]. Primer pairs designed to amplify only true POU5F1A and not its pseudogenes confirmed the expression of POU5F1A in embryonic carcinoma cells but failed to amplify PCR products from peripheral blood mononuclear cells (PBMNC), suggesting POU5F1A is not transcribed in these cells [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation